Clinical Outcomes And Risk Factors In Patients Circumcised By Chinese Shang Ring: A Prospective Study Based On Age And Types Of Penile Disease - Wang H; Huang Z; Zhou J; Zhang X; Liang C (Dove Medical Press, 2019)
Hui Wang,1–3 Zhenyu Huang,1–3 Jun Zhou,1–3 Xiansheng Zhang,1–3 Chaozhao Liang1–3 1Department of Urology, The First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 2The Institute of Urology, Anhui Medical University, Hefei, People’s Republic of China; 3Anhui Province Key Laboratory of Genitourinary Diseases, Anhui Medical University, Hefei, People’s Republic of ChinaCorrespondence: Chaozhao LiangDepartment of Urology, The First Affiliated Hospital of Anhui Medical University, Hefei 230022, People’s Republic of ChinaTel +86 551 6292 3440Fax +86 551 6363 3742Email liang_chaozhao@ahmu.edu.cnPurposes: To explore the efficacy of circumcision with Chinese Shang Ring (CSR) in the different cohorts so that can obtain the best applicable population and manage complications better.Methods: This study consisted of 657 patients who were circumcised with CSR in our institute between August 2017 and August 2018. All cases were followed up at post-operation for 3 to 15 months. The surgery time (ST), wound healing time (WHT), satisfaction with the appearance of postoperative penis and complications were collected and comparatively analyzed. Multivariate analysis was used to determine the independent risk factors associated with efficacy, which were presented by odd ratios and its 95% confidence index.Results: All cases wore the CSR successfully. The ST and WHT respectively were 5.75 ± 2.27 mins and 21.15 ± 5.05 days. The long-term complications, total complications (TC), satisfaction and successful circumcision (SC) respectively were 5.30%, 11.70%, 97.70% and 94.70%. For TC and SC, there was a difference between phimosis and redundant foreskin (21.30% vs 6.20%, P<0.001 and 89.20% vs 97.8%, P<0.001, respectively). In terms of satisfaction and SC, adolescents were higher than children (98.70% vs 94.70%, P=0.035 and 96.80% vs 90.10%, P=0.024, respectively) but was similar to adults (98.70% vs 100.00%, P=0.071 and 96.80% vs 98.00%, P=0.257, respectively). The degree of pain and the incidence of wound dehiscence in adults was higher than adolescents (P<0.05). The phimosis (OR= 1.47, 95% CI=1.26–1.79, P<0.001) and childhood (OR= 1.13, 95% CI =1.06–1.36, P<0.001) were associated with poor efficacy.Conclusion: The curative effect of circumcision by CSR in adolescents was similar to adults, both higher than that of children. However, adults have more severe pain and a higher probability of wound dehiscence in the later stage than adolescents. So, adolescence is probably the best time to be circumcised with CSR.Keywords: redundant foreskin, phimosis, age, sizes, Chinese Shang Ring